Hate Crime and Place: The Spatial and Temporal Concentration of Bias-Motivated Crime in Washington, D.C. - Wenger, Marin R. (Journal of interpersonal violence, 2022)
Prior research suggests that many crime types are spatially concentrated and stable over time. Hate crime, however, is a unique crime type that is etiologically distinct from others. As such, examination of hate crime from a spatial and temporal perspective offers an opportunity to understand hate crime and the spatial concentration of crime more generally. The current study examines the spatial stability of hate crimes reported to the police in Washington, D.C., from 2012 through 2018 using street segments, intersections, and block groups as units of analysis. Findings reveal that hate crime is spatially concentrated, with less than 4% of street segments and intersections experiencing hate crime over the study period. Results reveal a high degree of spatial stability, both year-to-year and over the long term even when restricting the analysis to units that experienced at least one hate crime.